Larval, pre-juvenile and juvenile development of Diapterus peruvianus (Perciformes: Gerreidae) - Jiménez Rosenberg, Sylvia Patricia; González Navarro, Enrique; Saldierna Martínez, Ricardo Javier (Revista de Biología Tropical, 2003)
The development of Diapterus peruvianus (Sauvage 1879) is based on 60 larvae collected in superficial tows made in Bahía Concepción, and on 16 pre-juvenile and juvenile organisms collected in Bahía de La Paz, B. C. S., México, using a standard plankton net and a rectangular epibenthonic net, respectively. Larvae of D. peruvianus show three large blotches on the dorsum of the gut that can fuse together and give the appearance of one large continuous blotch. There are two to three pre-anal pigments and 16 post-anal pigments in the ventral midline; cephalic pigments are present from the postflexion stage, as well as a serrated preoperculum. The prejuvenile and juvenile organisms are distinguished by their body depth, the anal-fin formula, the serrated preoperculum and the base pigments in the dorsal and anal fins.